Determinação de genes mórbidos e drogáveis a partir da construção e análise da rede integrada de interações moleculares entre genes humanos - Costa, Pedro Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The discovering process of new morbid genes and new target proteins for drugs have been shown to be very costly and laborious. Having in view cutting costs and speeding up this process, we propose, in this work, a new method to determine the gene druggability score and morbidity score, the probabilities of the protein encoded by the gene have the characteristics that make it a new target for drugs and in case of an alteration in that gene, we observed a phenotype that characterizes a genetic based illness. To determine these characteristics, we built, analyzed and determined the characteristics of the topology of the integrated molecular interactions network among human genes containing physical interactions between proteins, metabolic interactions and interactions of transcriptional regulation, and included other data such as level of gene transcription and cellular localization of the protein encoded by the gene. We tested our model in training sets and achieved results equal or better than the ones achieved by similar methods in the literature. Finally, with the purpose of investigating whether the assigned scores resembles the potential druggabilities and morbities of the previously unclassi ed genes, we looked for evidences in biomedical literature supporting the potential druggability and morbidity status of genes with the 10 highest scores. We found clear evidences for 73% and 90% of potential druggable and morbid genes respectively

O processo de descoberta de novos genes m orbidos e de novas prote nas alvo para drogas e atualmente muito custoso e laborioso. Visando diminuir os custos e acelerar esse processo, propomos, neste trabalho, um m etodo in silico para determina c~ao do grau de drogabilidade e do grau de morbidade de um gene, medidas da probabilidade da prote na codi cada pelo dado gene possuir caracter sticas que a tornariam alvo para novas drogas e da probabilidade de em caso de ocorr encia de altera c~ao do dado gene, o fen otipo observado caracterizar uma doen ca com base gen etica. Para determinar essas caracter sticas, constru mos, analisamos e determinamos os dados da topologia da rede integrada de intera c~oes moleculares entre genes humanos, contendo intera c~oes f sicas entre prote nas, intera c~oes metab olicas e intera c~oes de regula c~ao transcricional, e inclu mos outros dados, como n vel de transcri c~ao g enica e localiza c~ao celular da prote na codi cada pelo gene. Os ndices de acerto obtidos para os conjuntos de teste foram iguais ou superiores aos obtidos por m etodos semelhantes encontrados na literatura. Finalmente, buscamos na literatura biom edica evid encias de que os genes classi cados com os 10 maiores graus de drogabilidade e morbidade, exclu dos os j a conhecidamente drog aveis/m orbidos, possu am potencial para tal caracter stica, encontrando-as em 73% e 90% dos casos, respectivamente
Keywords: Genes; Aprendizado de máquina; Fisica medica; Medicamentos - Controle de custo